2006
DOI: 10.1002/ange.200502698
|View full text |Cite
|
Sign up to set email alerts
|

Apoptolidin: Induktion von Apoptose durch einen Naturstoff

Abstract: Der Naturstoff Apoptolidin führt selektiv bei bestimmten Krebszelllinien zum programmierten Zelltod. Dieser auch als Apoptose bezeichnete Vorgang ist ein wichtiger zellbiologischer Mechanismus zur Regulation von Homöostase und Morphogenese. Apoptotische Fehlregulationen sind mit verschiedenen Krankheiten verknüpft, insbesondere Krebs. Der extrinsische Weg zur Apoptose führt über Todesliganden und Todesrezeptoren zur Aktivierung einer Caspase‐Kaskade, die den proteolytischen Abbau der Zellarchitektur bewirkt. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 201 publications
0
10
0
Order By: Relevance
“…Representative examples for the importance of the sugar moiety are the cardiac glycosides (uptake, distribution and binding activity), macrolide antibiotics (ribosome binding) and the anthracyclines (DNA interaction) 2. The ability of apoptolidin A ( 1 ) to selectively induce apoptosis (programmed cell death) in tumor cells also depends on the presence of the glyco residues 3. The apoptolidins (A 1 , B 2 and C 3 ) form a group of 20‐membered ring macrocyclic natural products with 6‐deoxy‐4‐ O ‐methyl‐ L ‐glucose ( 4 ) attached to O‐9 and a disaccharide consisting of L ‐olivomycose ( 5 ) and D ‐oleandrose ( 6 ) linked to O‐27 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Representative examples for the importance of the sugar moiety are the cardiac glycosides (uptake, distribution and binding activity), macrolide antibiotics (ribosome binding) and the anthracyclines (DNA interaction) 2. The ability of apoptolidin A ( 1 ) to selectively induce apoptosis (programmed cell death) in tumor cells also depends on the presence of the glyco residues 3. The apoptolidins (A 1 , B 2 and C 3 ) form a group of 20‐membered ring macrocyclic natural products with 6‐deoxy‐4‐ O ‐methyl‐ L ‐glucose ( 4 ) attached to O‐9 and a disaccharide consisting of L ‐olivomycose ( 5 ) and D ‐oleandrose ( 6 ) linked to O‐27 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Apoptolidins A–E are a family of macrolide natural products that have attracted considerable attention as highly selective apoptosis regulators 1. The critical need for achieving greater selectivity in cancer chemotherapeutics has stimulated efforts to elucidate the mechanistic and structural basis for the apoptolidin’s unique pharmacological profile.…”
Section: Methodsmentioning
confidence: 99%
“…Some compounds appear to be rather promising with IC 50 values close to 1 mmol L À1 (or even lower), which is a concentration that might well be achieved as a systemically relevant therapeutic dose. [6][7][8][9][10] Many others, however, exhibit IC 50 values that are clearly higher than 10 mmol L À1 and, in some instances, even approach the millimolar range. [11][12][13][14] In the present study a group of seven indoloquinolizidine derivatives was identified on the basis of functional screening of approximately 11 000 natural-product derived and inspired compounds, which with IC 50 values close to 2 mmol L À1 , inhibited proliferation in different cell lines and increased the amount of apoptotic cells by up to 600 % as compared to the control value.…”
Section: Introductionmentioning
confidence: 99%